The role of Coriandrum sativum in treatment of kidney lesions that induced by Toxoplasma gondii in male rats (Texas Journal of Agriculture and Biological Sciences, 2023)
The purpose of this study was to demonstrate how an anti-parasitic drug can be obtained from an aqueous extract that was taken from the leaves of Coriandrum sativum and used to test the viability of Toxoplasma gondii. In this study, a total of 20 male rats were used, divided into the following four groups (with each group containing four rats): The normal saline was administered to the rat in the oral route. T. gondii tissue cysts were administered intraperitoneally into a rat in a volume of one milliliter containing one hundred tissue cysts. The extract of Coraindrium sativum was given to the rat every day via oral administration at a dose of 250 mg/kg body weight. A rat was given an intraperitoneal injection of 1 milliliter of T. gondii tissue cysts and then given an extract of leaves at a dosage of 250 milligrams per kilogram of body weight each day for a period of 30 days. When compared with control rats, the study's findings showed a substantial (P